Integration of Earth‐Abundant Catalysts on Si Solar Cells for Overall Solar Hydrogen Production. Issue 6 (27th March 2021) - Chen, Hongjun; Tran-Phu, Thanh; Phang, Pheng; Bo, Renheng; Yan, Di; MacDonald, Daniel; Tricoli, Antonio
Abstract : Development of low‐cost and earth‐abundant metal catalysts, as alternative to noble metals, is a promising approach for direct hydrogen production from solar light with integrated photoelectrochemical devices. Herein, a mild electrochemical method is used to directly synthesize two earth‐abundant catalysts, namely, CoP and CoSe, on planar‐junction p + nn + ‐Si solar cells. It is observed that the CoP–Si photocathodes achieve the best performance with ≈12 h of stability, a photocurrent density of up to 38 mA cm −2 at 0 V versus the reversible hydrogen electrode (RHE), and an onset potential of 488 mV versus RHE, and one of the most efficient solar‐driven hydrogen generation from earth‐abundant systems to date. Overall solar water splitting is also demonstrated in a tandem device configuration with a top TiO2 nanorod arrays photoanode achieving more than 5 h continuous hydrogen production. These results demonstrate the feasibility of using low‐cost earth‐abundant materials and the established Si solar cells technology for direct water splitting powered from sunlight. Abstract : A mild and convenient light‐assisted electrochemical method is used for the deposition of earth‐abundant CoP catalysts on Si photocathode, which demonstrates one of the most efficient solar‐driven hydrogen generation from earth‐abundant systems to date. It demonstrates the potential of earth‐abundant catalysts as substitution of noble metal catalyst for renewable hydrogen production from sunlight.